COVID-19-Associated Subacute Thyroiditis: Evidence-Based Data From a Systematic Review - Trimboli, Pierpaolo; Cappelli, Carlo; Croce, Laura; Scappaticcio, Lorenzo; Chiovato, Luca; Rotondi, Mario (Frontiers in Endocrinology, 2021)
Subacute thyroiditis (SAT) is a thyroid disease of viral or post-viral origin. Whether SAT represents a complication of Coronavirus-disease-2019 (COVID-19) caused by the Severe-acute-respiratory-syndrome-Coronavirus-2 (SARS-CoV-2) is still unclear. Our aim was to systematically review the literature to 1) explore size of the literature about SAT in COVID-19; 2) evaluate the clinical characteristics of SAT. PubMed/MEDLINE, Embase, and Scopus were searched until April 20th, 2021. Original papers, case report and case series reporting SAT in COVID-19 patients were included. Authors and their country, journal, year of publication, COVID-19 and SAT clinical presentation, thyroid function, therapy and follow-up data were extracted. Nineteen papers (17 case report and two case series) were included, describing 27 patients, 74.1% females, aged 18 to 69 years. COVID-19 was diagnosed by nasopharyngeal swab in 66.7% cases and required hospitalization in 11.1%. In 83.3% cases SAT occurred after COVID-19. Neck pain was present in 92.6% cases and fever in 74.1%. Median TSH, fT3 and fT4 were 0.01 mU/L, 10.79 pmol/L, and 27.2 pmol/L, respectively. CRP and ESR were elevated in 96% of cases. Typical ultrasonographic characteristics of SAT were observed in 83.3% of cases. Steroids were the most frequent SAT therapy. Complete remission of SAT was recorded in most cases. In conclusion, the size and quality of published data of SAT in COVID-19 patients is poor, being available only case report and case series. SAT clinical presentation in COVID-19 patients seems to be similar to what is generally expected.